Possibilities for implementing of anti-fibrotic and anti-inflammatory effects of metabolic therapy in acute alcoholic disorders under experimental conditions - Rykalo, N. A.; Romanenko, I. V. (Zaporozhye Medical Journal, 2022)
The aim of the work was to study antifibrotic and anti-inflammatory effects of metabolic therapy and mechanisms of regeneration in acute alcoholic liver damage (AALD) in rats under experimental conditions. Materials and methods. The experiment involved 66 white non-linear male rats with a mass of 120–130 g, which were divided into 5 groups: 1 – intact animals (n = 10); 2 – animals with AALD (n = 20), 3 – animals (n = 12) with AALD and intraperitoneally injected with Corvitin, 4 – animals (n = 12) with AALD and injected with Glutargin, 5 – аnimals with AALD (n = 12) and injected with Corvitin and Glutargin. The pro-inflammatory cytokines and cell cycle phases were analyzed. Results. The level of IGF-1 was significantly 24.1 % higher in group 2 compared to the control. In animals of group 3, the level of IGF-1 was 20.2 % decreased compared with group 2. The level of IGF-1 was significantly 9.7 % decreased in group 5 animals compared with group 2. There was a 31.6% increase in the level of TGF-β in animals of group 2 in comparison with the control ones. The level of TGF-β was 22.8 % decreased in group 3 compared with group 2. In group 5 animals, the value was 12.0 % lower than in group 2. The percentage of cell nuclei in the presynthetic phase in group 2 rats was 8.3 % higher than in controls. In animals of group 2, the number of cell nuclei in the phase of DNA synthesis were 33.3 % larger than in group 1. The rate of DNA fragmentation in AALD exceeded the corresponding value in control group by 27.5 %. Conclusions. AALD was accompanied by an increase in the serum IGF-1 and TGF-β in animals. The administration of corvitin decreased the level of IGF-1 in rats with AALD, and the use of glutargine mainly decreased the level of TGF-β. Combined use of the drugs did not show significant effectiveness. Compensatory regeneration mechanisms were activated in AALD processes and apoptotic cell death was evidenced by the increased indicators of nuclear DNA fragmentation.